Characteristics and outcomes for pulmonary aspergillosis in critically ill patients without influenza: A 3-year retrospective study - Chien-Ming Chao; Chih-Cheng Lai; Khee-Siang Chan; Chun-Chieh Yang; Chin-Ming Chen; Chung-Han Ho; Hsuan-Fu Ou; Wen-Liang Yu (Elsevier, 2023)
Background: Previous studies have revealed higher mortality rates in patients of severe influenza coinfected with invasive pulmonary aspergillosis (IPA) than in those without the coinfection; nonetheless, the clinical outcome of IPA in critically ill patients without influenza remains unclear. Patients and methods: This retrospective study was conducted in three institutes. From 2016-2018, all adult patients diagnosed with IPA in the intensive care units (ICUs) were identified. The logistic regression was used to identify the potential risk factors associated with in-hospital mortality in patients with non-influenza IPA. The stratified analysis of IPA patients with and without antifungal therapy was also performed. The final model was established using a forward approach, selecting variables with p-values less than 0.05. Results: Ninety patients were included during the study period, and 63 (70%) were men. The most common comorbidity was diabetes mellitus (n = 24, 27%), followed by solid cancers (n = 22, 24%). Antifungal therapy was administered to 50 (56%) patients, mostly voriconazole (n = 44). The in-hospital mortality rate was 49% (n = 44). Univariate analysis revealed that the risk factors for mortality included daily steroid dose, APACHE II score, SOFA score, C-reactive protein (CRP) level, carbapenem use, antifungal therapy, and caspofungin use. Multiple regression analysis identified four independent risk factors for mortality: age (Odds ratio [OR], 1.052, p = 0.013), daily steroid dose (OR, 1.057, p = 0.002), APACHE II score (OR, 1.094, p = 0.012), and CRP level (OR, 1.007, p = 0.008). Furthermore, the multivariable analysis identified that more physicians would initiate antifungal therapy for patients with prolonged steroid use (p = 0.001), lower white blood cell count (p = 0.021), and higher SOFA score (p = 0.048). Thus, under the selection bias, the independent risk factors for mortality in the antifungal treatment subgroup were daily steroid dose (OR, 1.046, p = 0.001) and CRP (OR, 1.006, p = 0.018), whereas the independent risk factor for mortality in the untreated group became APACHE II score (OR, 1.232, p = 0.007). Conclusions: Patients with IPA had a substantially high mortality. Overall, age, steroid use, APACHE II score, and CRP level were identified as the independent risk factors for mortality in patients in the ICU.